Songket Travel Organizer (SOTRA) - Noralisa, Ismail; Norazlina, Rahmat; Norzaidah, Ngali; Norazidah, Shamsudin (Department of Research, Industrial Linkages & Alumni, 2014)
Travelling is a stimulating activity which been awaited by most people. Regardless in the origin country or outside, this activity requires people to carry several stuffs such as identification card, passport, flight ticket, boarding pass, credit card, cash, ATM cards and mobile phone. The handling devours a possibility of misplace or worse, missing things especially for disorganized people. Therefore, a proper travel organizer can help travelers to place all their belongings for easy retrieval. Hence, Songket Travel Organizer (SOTRA) is an essential travel organizer to suit the needs of travelers. The main advantage of SOTRA is the multi-size compartment for various traveling items. Another important element is it’s made for waterproof which suit all weathers and use traditional Malay fabric which is Songket as a covering theme. Songket has been chosen due to the lack usage of this fabric currently. Nowadays, the use of this fabric is limited to special occasions only such as wedding, Aidilfitri celebration or cultural performances. This is due to the nature of the fabric which insists proper care and furthermore, it's not comfortable for leisure wear. For that reason, it’s been dropped as an attire choice hence resulted in neglection by young generation. If the ignorance continuously occurs, this exclusive fabric which represents Malaysian culture might be forgotten by future generation. Thus, there is a need to introduce Songket in a different usage form besides use it as apparel. Travel organizer been chosen as a product for promoting Songket because it been widely used by travellers who travel locally and internationally. This could be further realized through collaboration with local airlines such as Malaysia Airlines and Tourism Malaysia. As a conclusion, SOTRA could be a solution for proper storage of travel items and help to promote and ensure the sustainability of Songket.